Validity and reliability of the scale of attitudes toward statistics - Antón Pérez, Juan Manuel (2019)
The objective of the research was to determine the validity and reliability of a new Attitude Scale towards Statistics, constructed by the authors of the present investigation based on the Auzmendi Scale, which postulates the presence of an Ethical Dimension, applied to Engineering students and Social Sciences of the National University "Pedro Ruiz Gallo" of Lambayeque, academic semester 2016 II. The research was quantitative - social technology and the design was that of a prospective Cohort; study population was constituted by 10 175 students of the mentioned Professional Schools who took at least 1 course of Statistics or are taking it; the sample was of 584 students divided proportionally and chosen with systematic sampling. The authors substantially modified the wording of several items of the Auzmendi Scale, canceled others and in some items the modification was in a way to clearly express the attitude that was sought to be collected; in addition, the authors postulated that the Test of Attitudes toward Statistics should have an Ethical dimension, for which they constructed 5 new items. An exploratory factor analysis was carried out, with a reduction in the dimensionality of the main components and the varimax rotation method. The investigation confirmed the presence of an Ethical dimension, with an internal consistency of 92.4%. The Scale of Attitudes towards Statistics constructed by the authors based on the Auzmendi Scale presented a satisfactory construct validity and high reliability.